THE ARCHETYPE OF SUSI'S COLLECTIVE UNCONSCIOUS IN THE NOVEL “KEJATUHAN DAN HATI” BY SITI ROEKIAH THE PSYCHOLOGY OF CARL GUSTAV JUNG - Satriani, Irma (Journal of Language, Literature and Teaching, 2025)
His study will describe the collective unconsciousness of archetypes in the character of Susi in the novel Kejatuhan dan Hati by Siti Roekiah. This study will use a descriptive qualitative method with data sources in the form of narrative and dialogue quotations that show four archetypes in the character of Susi. Data collection will be carried out using the observation and note-taking technique, which involves reading the data sources thoroughly, then recording the narrative and dialogue data in the novel. The collected data will then be entered into a data classification table for analysis through Jung's psychological perspective.The results of this study found that Susi's Persona is her true self when she has to behave according to her mother's wishes. Then, Susi's Shadow began to emerge when she realized that her mother had gone too far by forcing her to marry, followed by her Animus when Susi decided to join a movement that changed her into a personality that was very different from her former self. However, Susi never achieves Self within herself by the end of the novel because she remains bound by her ego.